TESTING OF WIRELESS SCENARIO FOR DIFFERENT ENVIRONMENT - J. S. Awati; Dr. M. R. Patil; Dr. S. A. Patil (International Journal of Innovations in Engineering Research and Technology, 2021)
Wireless sensor Networks are widelyused. Before actual deployment of wireless scenario in real time field, testing of the scenario is very important. With the help of Qualnet simulator the different geographical environment can be created which will support to reduce real time problemsfacing afterimplementationof wireless sensor networks. This paper deals with the testing of wireless scenario for different geographical environment. Scenario considered withnine nodes with different routing protocols anda variety ofenvironment. The parameters considered are average end to end throughput, average end to end delay, total data received and average jitter.